Estuary contexts and governance models in the new climate era, New South Wales, Australia - Thom, Bruce; Hudson, John; Dean-Jones, Pam (Frontiers in Environmental Science, 2023)
Estuaries along the southeast coast of Australia form distinctive biophysical types. Each type reflects both geological setting and a Holocene geomorphic history associated with the degree of infill driven by marine and terrestrial processes. Of the 180 estuaries found within the state of New South Wales (NSW) many occur in national parks or are not significantly modified by human activities. For those estuaries where human activities are directly impacting environmental conditions and social, cultural and economic functions of the waterways, the management challenge is more complex. We combine the biophysical and socio-economic characteristics for the NSW coast to identify four “estuary contexts”, referred to as: (1) intermittently closed and open lakes and lagoons (ICOLLs), (2) coastal lakes, (3) deltaic floodplains, and (4) drowned river valleys. Each context may require different governance arrangements to address the coastal management requirements as outlined in recently introduced NSW legislation and planning policy. Such arrangements become especially urgent given threats facing private and public assets in low-lying locations around the shores of these estuaries as sea level continues to rise and climate change adaptation strategies set out in local government Coastal Management Programs are developed and implemented.